2017
DOI: 10.1002/2016ja022700
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and testing of wide‐field UV instruments

Abstract: As with all optical systems the calibration of wide‐field ultraviolet (UV) systems includes three main areas: sensitivity, imaging quality, and imaging capability. The one thing that makes UV calibrations difficult is the need for working in vacuum substantially extending the required time and effort compared to visible systems. In theory a ray tracing and characterization of each individual component of the optical system (mirrors, windows, and grating) should provide the transmission efficiency of the combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The absolute calibration and its corrections for the sensitivity decrease are difficult problems for satellite instruments performing measurements in the UV range (see, e.g., Quémerais et al 2013or Frey et al 2017. As discussed recently by Baliukin et al (2019) and Koutroumpa et al (2019), the SOHO/SWAN instrument showed a significant sensitivity degradation from 2008 to 2014, which can be…”
Section: Solar Far-ultraviolet/extreme-ultraviolet Anisotropymentioning
confidence: 97%
“…The absolute calibration and its corrections for the sensitivity decrease are difficult problems for satellite instruments performing measurements in the UV range (see, e.g., Quémerais et al 2013or Frey et al 2017. As discussed recently by Baliukin et al (2019) and Koutroumpa et al (2019), the SOHO/SWAN instrument showed a significant sensitivity degradation from 2008 to 2014, which can be…”
Section: Solar Far-ultraviolet/extreme-ultraviolet Anisotropymentioning
confidence: 97%
“…Before integration of the FUV instrument into the ICON satellite, a dedicated calibration campaign was performed (Frey et al. 2017 ) which determined not only the geometric imaging properties of the system but also the passbands, field of view, out of band contributions from scattering, and the overall quantitative sensitivity of the system (Mende et al. 2017 ).…”
Section: Altitude Profile Data Collectionmentioning
confidence: 99%
“…One of the most important properties of the instrument is its passband and its response to photons of different wavelengths (Frey et al. 2017 ). The careful characterization of the pass band allows then for an on-orbit confirmation or improvement of the calibration accuracy by using regular observations of bright early type-B UV stars (Frey et al.…”
Section: Radiometric Calibration: Theorymentioning
confidence: 99%
See 2 more Smart Citations